Evidence from Ethiopia: Alternative formation of rural savings and credit cooperatives and their implications - Abay, Kibrom A.; Koru, Bethlehem; Abate, Gashaw T.; Berhane, Guush (London School of Economic and Political Science, 2017)
What is the optimal size and composition of Rural Savings and Credit Cooperatives (RuSACCOs)? With these broader questions in mind, we characterize alternative formation of RuSACCOs and their implications in improving rural households’ access to financial services, including savings, credit and insurance services. We find that some features of RuSACCOs have varying implications for delivering various financial services (savings, credit and insurance). We find that the sizes of RuSACCOs have nonlinear and varying implications across the various financial services that RuSACCOs provide. We also find that compositional heterogeneity among members (including diversity in wealth) improves members’ access to credit, while this has little (no) implication in improving households’ savings behavior. Similarly, strong social cohesion among members is shown to improve households’ access to financial services, particularly savings and credit access. These empirical characterizations suggest that the optimal size and composition of RuSACCOs may vary across the domains of financial services they are meant to provide. These pieces of evidence provide some new insights on how to ensure financial inclusion among smallholders in remote and rural areas, a pressing agenda and priority of policy makers in developing countries, including Ethiopia. The results also provide some insights into rural microfinancing operations and saving cooperatives which are struggling to improve their customers’ saving rates.